Street Trading and Urban Distortion: Rethinking Impacts and Management Approaches from Urban Planners’ Perspective in Enugu City, Nigeria: Viewing Street Vending Activities from the Lens of Orderliness and Economic Gain - John-Nsa, Chioma; Onyebueke, Victor; Enemuo, Ebube (Alanya Üniversitesi, 2023)
This study investigates the relationship between street trading and urban planning in Enugu City, Nigeria, within the expanding informal economy of the global South. It particularly focuses on the perspectives of urban planners regarding the impacts and management of street trading. The research employed a mixed-method approach, including personal observation, questionnaires, and in-depth interviews, analyzed through basic statistical methods. Findings reveal that urban planners recognize the socio-economic importance and cultural relevance of street trading, despite its negative spatial externalities. Contrary to prevailing assumptions, planners favour negotiated solutions over forced evictions. This study highlights the need for inclusive urban planning practices that accommodate the socio-economic benefits of street trading while addressing its challenges, contributing to the discourse on sustainable urban development.